Diagnósticos de abdomen agudo en el Centro de Salud Velasco Ibarra 2018 Machala El Oro Ecuador. - Riofrio Estrella, Dayana Brigitte (Machala : Universidad Técnica de Machala, 2019)
Acute abdominal pain is a symptom that occurs suddenly and depending on the origin can be visceral, somatic or referred. The acute abdomen is defined as the set of signs and symptoms, where the predominant symptom is abdominal pain of sudden and insidious onset, with an evolution less than 24 hours. It is a painful, progressive syndrome that produces local and systemic alterations that are going to depend on the etiology and evolution of the clinical picture and can cause the death of the patient. For a correct diagnosis, a complete history and adequate physical examination are necessary, to show the presence of abdominal signs and symptoms associated with an acute abdomen. The objective of our research is to identify the incidence and perform the statistical analysis of the acute abdomen diagnosed in the emergency area of the Health Center “Velasco Ibarra” during the year 2018. Our research was a retrospective, longitudinal study, with analytical phases, in the period from January 1 to December 31, 2018 for which we use the statistical database of the health center, upon request and approval of the District Department 07D02 Machala-Salud and the head of the type C health center “Velasco Ibarra " Our research included 546 patients who came with acute abdominal pain and the months with the greatest concurrence were August, November and December, this can be multifactorial: high-fat diet, causing acute gallstones, consumption of alcoholic beverages during celebrations held during These months of the year causing pictures of acute pancreatitis, ingestion of vegetables and fruits with seeds which can be the origin of fecalites, conditioning the appearance of acute obstructive appendicitis and the presence of spicy and strong condiments that could cause pictures of acute gastritis.
El dolor abdominal agudo es un síntoma que se presenta de forma súbita y según el origen puede ser visceral, somático o referido. El abdomen agudo se define como el conjunto de signos y síntomas, en donde el síntoma predominante es el dolor abdominal de inicio súbito e insidioso, con una evolución menor de 24 horas. Es un síndrome doloroso, progresivo, que produce alteraciones locales y sistémicas que van a depender de la etiología y evolución del cuadro clínico y puede ocasionar la muerte del paciente. Para un correcto diagnóstico es necesario una anamnesis completa y una adecuada exploración física, evidenciar la presencia de signos abdominales y de síntomas asociados a abdomen agudo. El objetivo de nuestra investigación es identificar la incidencia y realizar el análisis estadístico del abdomen agudo diagnosticado en el área de emergencia del Centro de Salud “Velasco Ibarra” durante el año 2018. Nuestra investigación fue un estudio retrospectivo, longitudinal, con fases analíticas, en el período del 1 de enero al 31 de diciembre del 2018 para lo cual utilizamos la base de datos estadística del centro de salud, previa solicitud y aprobación de la Dirección Distrital 07D02 Machala-Salud y del responsable del centro de salud tipo C “Velasco Ibarra”. Nuestra investigación incluyó 546 pacientes que acudieron con dolor abdominal agudo y los meses con mayor concurrencia fueron agosto, noviembre y diciembre, esto puede ser multifactorial: alimentación rica en grasas, originando cuadros biliares agudos, consumo de bebidas alcohólicas durante las celebraciones que se realizan durante estos meses del año originando cuadros de pancreatitis aguda, ingestión de vegetales y frutas con semillas las cuales pueden ser origen de fecalitos condicionando la aparición de una apendicitis aguda obstructiva y la presencia de picantes y condimentos fuertes que podrían originar cuadros de gastritis aguda .
Keywords: DOLOR ABDOMINAL; DIAGNOSTICO; ABDOMEN AGUDO; SINTOMAS